Laing early onset distal myopathy: slow myosin defect with variable abnormalities on muscle biopsy. Issue 2 (15th August 2005) - Lamont, P J; Udd, B; Mastaglia, F L; de Visser, M; Hedera, P; Voit, T; Bridges, L R; Fabian, V; Rozemuller, A; Laing, N G
Abstract : Background: Laing early onset distal myopathy (MPD1) is an autosomal dominant myopathy caused by mutations within the slow skeletal muscle fibre myosin heavy chain gene, MYH7 . It is allelic with myosin storage myopathy, with the commonest form of familial hypertrophic cardiomyopathy, and with one form of dilated cardiomyopathy. However, the clinical picture of MPD1 is distinct from these three conditions. Objective: To collate and discuss the histological features reported in the muscle biopsies of MPD1 patients and to outline the clinical features. Results: The phenotype of MPD1 was consistent, with initial weakness of great toe/ankle dorsiflexion, and later development of weakness of finger extension and neck flexion. Age of onset was the only variable, being from birth up to the 20s, but progression was always very slow. The pathological features were variable. In this retrospective series, there were no pathognomonic diagnostic features, although atrophic type I fibres were found in half the families. Rimmed vacuoles are consistently seen in all other distal myopathies with the exception of Myoshi distal myopathy. However, they were found in a minority of patients with MPD1, and were not prominent when present. Immunohistochemical staining for slow and fast myosin showed co-expression of slow and fast myosin in some type I fibres, possibly indicating a switch to type II status. This may be a useful aid to diagnosis. Conclusions: The pathological findings in MPD1 are variable and appear to be affected by factors such as the specific muscle biopsied, the age of the patient at biopsy, and the duration of disease manifestations.